Label‐Free Optofluidic Nanobiosensor Enables Real‐Time Analysis of Single‐Cell Cytokine Secretion. Issue 26 (28th May 2018) - Li, Xiaokang; Soler, Maria; Szydzik, Crispin; Khoshmanesh, Khashayar; Schmidt, Julien; Coukos, George; Mitchell, Arnan; Altug, Hatice
Abstract: Single‐cell analysis of cytokine secretion is essential to understand the heterogeneity of cellular functionalities and develop novel therapies for multiple diseases. Unraveling the dynamic secretion process at single‐cell resolution reveals the real‐time functional status of individual cells. Fluorescent and colorimetric‐based methodologies require tedious molecular labeling that brings inevitable interferences with cell integrity and compromises the temporal resolution. An innovative label‐free optofluidic nanoplasmonic biosensor is introduced for single‐cell analysis in real time. The nanobiosensor incorporates a novel design of a multifunctional microfluidic system with small volume microchamber and regulation channels for reliable monitoring of cytokine secretion from individual cells for hours. Different interleukin‐2 secretion profiles are detected and distinguished from single lymphoma cells. The sensor configuration combined with optical spectroscopic imaging further allows us to determine the spatial single‐cell secretion fingerprints in real time. This new biosensor system is anticipated to be a powerful tool to characterize single‐cell signaling for basic and clinical research. Abstract : In this study, a new nanoplasmonic biosensor for real‐time monitoring of single‐cell secretion is presented. The innovative label‐free system enables the dynamic spatiotemporal detection and quantification of protein secretion from single cells while maintaining controlled conditions for cell activity during hours and without any chemical disturbance of the cell environment.